2021
DOI: 10.1136/bmjophth-2020-000571
|View full text |Cite
|
Sign up to set email alerts
|

Elevated levels of prostaglandin E2in the tears of patients with severe allergic conjunctivitis and primary cultured conjunctival cells are suppressed by ketotifen and dexamethasone

Abstract: ObjectiveWe examined the production of prostaglandin E2 (PGE2), which is the key prostaglandin involved in inflammatory disorders of the ocular surface. Tears and conjunctival fibroblasts were evaluated in order to assess allergic inflammation and the effect of specific drugs.Methods and analysisPGE2 was measured in tears from both patients and normal volunteers. Primary cultures of human conjunctival fibroblasts were incubated with interleukin (IL)-4 and tumour necrosis factor (TNF)-α with or without ketotife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Results showed a statistically significant elevation ( P < 0.04) in the average tear PGE2 level in VKC patients (190 pg/ml) compared to control subjects (6.0 pg/ml). After a 4-week treatment of ketotifen fumarate and dexamethasone, the PGE2 levels were reduced in the VKC patients to a mean of 62.6 pg/ml ( P < 0.04), along with a decrease in symptoms [15]. These findings suggest that molecules involved in allergic processes contribute to ocular itch in individuals with allergic ocular surface disease.…”
Section: Nociceptive Itch and Nociceptive Painmentioning
confidence: 77%
“…Results showed a statistically significant elevation ( P < 0.04) in the average tear PGE2 level in VKC patients (190 pg/ml) compared to control subjects (6.0 pg/ml). After a 4-week treatment of ketotifen fumarate and dexamethasone, the PGE2 levels were reduced in the VKC patients to a mean of 62.6 pg/ml ( P < 0.04), along with a decrease in symptoms [15]. These findings suggest that molecules involved in allergic processes contribute to ocular itch in individuals with allergic ocular surface disease.…”
Section: Nociceptive Itch and Nociceptive Painmentioning
confidence: 77%
“…Yamanishi et al [24] found decreased production of PGE 2 in the tears of patients with severe conjunctivitis after dexamethasone administration. Fuller et al [40] reported that dexamethasone inhibits the production of thromboxane B 2 .…”
Section: Discussionmentioning
confidence: 98%
“…infection are associated with an ongoing inflammatory process. The proteins involved in this process are PGs, products of the reaction carried out by cyclooxygenases [23,24]. Under normal physiological conditions, PGs have crucial homeostatic functions, including maintaining IOP.…”
Section: Discussionmentioning
confidence: 99%
“…Leukotriene is a lipid mediator that causes vasodilation and increased permeability of conjunctival blood vessels [ 61 , 62 , 63 ]. Prostaglandin has been shown to intensify the ocular itch and cause dilation of conjunctival blood vessels [ 64 , 65 ]. Cytokines are small, secreted cell-signaling proteins that are released by both immune and non-immune cells.…”
Section: Mediators Of Allergymentioning
confidence: 99%